IMPLEMENTASI HAK DAN KEWAJIBAN APARATUR SIPIL NEGARA DI PENGADILAN TINGGI AGAMA SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 5 TAHUN 2014 - Muthia Eka Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTMuthia Eka Sari, NPM. 13.11.1001.1011.039, "Implementation of Rights and Obligations of State Civil Apparatus in High Religious Court of Samarinda Based on Law Number 5 Year 2014" guided by Mrs. Kunti Widayati, S.H., M.Hum and Mrs. Isnawati, S.H., M.H. This research was conducted to find and search data in an effort to answer the proposed legal problem where in the data, the author uses normative method from various literature sources such as library materials and research directly to the high court office of Samarinda religion and data is analyzed by using descriptive analysis, Which is very clear about the implementation of the rights and obligations of the State Civil Apparatus in the High Court of Religious Samarinda based on Law No. 5 of 2014 on State Civil Apparatus. The result of the research shows that based on Law Number 5 Year 2014, all employees of State Civil Apparatus must be obedient and obedient to the intended provisions. Rights and Obligations of Civil State Apparatus of the same validity to all employees in accordance with Article 21 of Law Number 5 Year 2014 is still there that has not been implemented or violated by the employees because it needs supervision and coaching by their respective leaders, With the number of Apparatus Civil State within the High Court of Samarinda Religion in 2017 as many as 274 employees where from 2014 until 2016 there are 2 employees who got disciplinary conditions with mandate promotion and cut performance allowances in accordance with Government Regulation no. 53 of 2010 on the Discipline of Civil Servants and Supreme Court Law Number 14 Year 1985.Keywords: Law Number 5 Year 2014 in High Court of Samarinda Religion